Anticonvulsant Mechanisms of Electroconvulsive Therapy and Relation to Therapeutic Efficacy. Issue 3 (September 2015) - Duthie, Ashleigh C.; Perrin, Jennifer S.; Bennett, Daniel M.; Currie, James; Reid, Ian C.
Abstract : Background: Electroconvulsive therapy (ECT) is held to confer anticonvulsant effects, although the role of rise in seizure threshold upon clinical effect is uncertain. This study investigated the relationship in a large, consecutive, retrospective sample of patients receiving ECT in Aberdeen. We have tested the hypotheses of previous authors to further examine the relationship between seizure and therapeutic effect as well as discuss the potential underlying neurobiological mechanisms. Methods: All patients receiving ECT at the Royal Cornhill Hospital between 2000 and the end of 2008 were identified from the Scottish ECT Accreditation Network. Electroconvulsive therapy was administered twice weekly with a bifrontotemporal electrode placement using routine dosage schedules. Data were gathered from the Scottish ECT Accreditation Network and case notes regarding ECT course and clinical effect. Results: The seizure threshold increased in 219 (94.4%) patients, stayed the same in 13 (5.6%) patients, and decreased in 0 patient (n = 232). No significant relationship was present between change in seizure threshold and change in Montgomery-Asberg Depression Rating Scale score ( P = 0.39; Kendall τ b r = 0.047; n = 182), although responders did display greater increase in seizure threshold than nonresponders. Conclusions: Electroconvulsive therapy confers anticonvulsant effects in a consecutive sample of real-life patients. Neither initial seizure threshold nor magnitude of seizure threshold increase is a predictor of clinical response to ECT. A rise in seizure threshold is not essential for therapeutic effect but may represent an important marker of underlying neuronal state. The evidence reviewed in this article supports a link between neuroplastic effects of ECT and the evidenced rise in seizure threshold.